Measuring gender inequality in household decision-making and its impact on food security: Evidence from rice-farming households in Jambi Province, Indonesia - Junaidi, Junaidi; Hardiani, Hardiani; Hastuti, Dwi (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2025)
This study investigates the impact of gender inequality in household decision-making on food security among rice-farming households in Jambi Province, Indonesia. Drawing on the Harvard and Moser Models, the research develops quantitative indicators of gender roles and applies an ordered probit model to assess household food security across ranked categories. Data were collected from 214 households using a two-stage stratified sampling method, combining survey responses with secondary institutional data. The findings reveal that only 29% of households are food secure, while 71% experience either temporary or chronic food insecurity. Male-dominated households are more likely to achieve food security, whereas female-dominated and jointly managed households are significantly more vulnerable. Structural factors also exert a decisive influence: the education of the household head and land ownership consistently enhance food security. At the same time, participation in farmer training without resource support and reliance on non-farm income have adverse effects. These results underscore the importance of gender-inclusive policies that expand women’s access to education, land, credit, and market information. Targeted microcredit programs, resource-supported training, and the promotion of joint decision-making are recommended to reduce gender inequality and strengthen sustainable food security in rural farming communities.